2003
DOI: 10.1007/bf02867386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic (Allium sativum L.) extract on degree of hydration, fructose, sulphur and phosphorus contents of rat eyelens and intestinal absorption of nutrients

Abstract: Influence of aqueous garlic extract on degree of hydration, fructose, sulphur and phosphorus contents of rat eyelens and intestinal absorption of nutrients were assessed. Inclusion of garlic extract in culture medium containing glucose and xylose inhibited the hydration of rat eyelens, whereas galactose evinced the reverse trend. Aqueous garlic extract in general decreased the concentration of fructose and phosphorus, whereas sulphur concentration increased when rat eyelenses, were incubated with galactose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…It is reported that L -Glutamate supplementation decreased HFD-deepened crypt depth, and enhanced the cell maturing rate and the secretory function of epithelial cells [40]. On the other hand, excessive consumption of garlic could result in the loss of intestinal epithelial cells [41], leading to the inhibition of intestinal absorption of glutamic acid, sucrose, and glucose [42], which might be the reason why garlic shortens the height of villi in a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that L -Glutamate supplementation decreased HFD-deepened crypt depth, and enhanced the cell maturing rate and the secretory function of epithelial cells [40]. On the other hand, excessive consumption of garlic could result in the loss of intestinal epithelial cells [41], leading to the inhibition of intestinal absorption of glutamic acid, sucrose, and glucose [42], which might be the reason why garlic shortens the height of villi in a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few bioactive OSCs have been extracted from Allium sp. by conventional procedures, mainly for analytical purposes and/or for the determination of biological activities (Arnault et al, 2003;Bocchini et al, 2001;Bose and Laha, 2013;Cavallito and Bailey, 1944;Gîtin et al, 2014;Han et al, 1995;Li et al, 2017;Mansor et al, 2016;Sekar et al, 2015;Songsungkan and Chanthai, 2014;Sood et al, 2003;Ueda et al, 1994). For instance, Ueda et al (1994) extracted trans-(+)-S-propenyl-L-cysteine sulfoxide (PeCSO), γ-glutamyl-PeCSO, and cycloalliin from onion.…”
Section: Conventional Extractionmentioning
confidence: 97%
“…Also Sood et al (14) reported alterations of brush border membrane, thinning and sloughing off of villous structures and vacuolization in jejunum of rats that were treated with garlic.…”
Section: Discussionmentioning
confidence: 98%
“…(2) However, excessive consumption of garlic could result in gastric mucosal erosion, reddening of the mucosa, and loss of intestinal epithelial cells. (3) Studies by Sood et al (14) showed that garlic intake led to inhibition of intestinal absorption of glutamic acid, sucrose and glucose. This research was aimed at studying the implications of excessive consumption of garlic on the histochemistry and functions of the small intestine.…”
Section: Introductionmentioning
confidence: 99%